Selective phosphate uptake in the presence of sulfate with granular spent coffee grounds-based adsorbents via metal oxide modification - Steiger, Bernd G. K.; Faleye, Adekunle C.; Babalola, Bolanle M.; Wilson, Lee D. (Frontiers in Environmental Chemistry, 2025)
Selective phosphate (Pi) remediation from saline aquatic environments is crucial in combating eutrophication. In this study, biocomposite adsorbents with 80% spent coffee grounds, variable chitosan content, and either 1% or 5% metal oxide (MO) content (-A = 1 wt.%; -B = 5 wt.%) were evaluated. The type of MO was either Fe2O3 (Fe-B or Fe-A) or Al2O3 (Al-B or Al-A). The material characterization of these biocomposites was achieved via thermogravimetry and spectroscopic techniques (13C NMR, FT-IR, and X-ray diffraction (XRD)). Composite formation and coordination between functional groups was evidenced by FT-IR spectral and XRD results. The role of sulfate as a competitor anion was evaluated due to its environmental significance. Single-component isotherm studies showed equilibrium adsorption capacities that range from ca. 13 mg/g–20 mg/g for phosphate and 9 mg/g–36 mg/g for sulfate. To investigate the selectivity of phosphate over sulfate, binary selectivity experiments (equal concentration) were conducted. The binary selectivity factor αt/c ranged from 14 to 16 for Al-based and from 6 to 9 for Fe-based composites. The adsorption capacity ratio was ca. 2–3 for Al-based and ca. 4 for Fe-based composites, which favor phosphate in the presence of sulfate (at 100 mg/L for both anions). This was verified through adsorption experiments in binary, ternary, and quaternary anion systems, where different adsorption sites account for the concerted anion adsorption. Kinetic studies according to the pseudo nth-order model for two selected composites showed a reaction order of ca. 1.6–1.8 for Al-A and Fe-B. Adsorption of phosphate in spiked river water with 10 mg/L phosphate (spiked) and ca. 80 mg/L sulfate (natural) for Al-A and Fe-B resulted in ca. 0.4 mg/g–0.5 mg/g uptake capacity of phosphate. Coordination of phosphate was inferred to follow inner-sphere complexation, in contrast to that of sulfate. In turn, this study demonstrates how granular adsorbents derived from food waste with high lignocellulose content can be modified with MO to yield phosphate-selective adsorption in saline aqueous media.